PERAN PENDIDIKAN AGAMA DALAM PEMBINAAN SELF CONTROL SISWA DI SDIT NURUL FIKRI ACEH - Hamdi Yusliani (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Self-control is one of the competencies which Elementary school students should have. This self-control competency is designed to review the concept of themselves as controllers for their own thoughts, feelings, and behavior, so the students can manage themselves to avoid delinquency, which is common in children at this elementary level. This research is qualitative research using descriptive methods, field research techniques, and library research. While the data collection techniques used observation, interviews, and questionnaires.  The results showed that the curriculum used at SDIT Nurul Fikri Aceh includes two models, namely the formal curriculum (Diknas and the typical SIT curriculum) and the hidden curriculum in the form of inculcating values. The implementation of PAI Learning in improving students' self-control skills at SDIT Nurul Fikri Aceh includes 1) PAI learning in class is face-to-face activities by developing learning methods and strategies with preliminary activities, core activities, and core closing activities. 2) PAI learning outside the classroom is fostering student self-control through religious activities.